Penerapan Model Quantum Teaching untuk Meningkatkan Hasil Belajar Siswa Kelas XI IPS - Bella Pratiwi Utami; Iskandar Syah; Suparman Arif (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2017)
The purpose of this study is to find out "whether there is an improvement or no improvement on cognitive learning outcome in History subject for students of class XI Social Sciences at Senior High School 1 Punggur academic year of 2016/2017 after taught using Quantum Teaching model". The method used in this research was experimental research method with The One-Shot Case Study design. The data collection was done through testings. The data was calculated manually using the percentage formula. The results of the data analysis showed that there was an improvement in students' learning outcome after taught using Quantum Teaching model.Tujuan penelitian ini untuk mengetahui Ada atau tidak ada peningkatan hasil belajar kognitif pada mata pelajaran sejarah siswa kelas XI IPS di SMA Negeri 1 Punggur Tahun Pelajaran 2016/2017 setelah menggunakan model Quantum Teaching. Metode yang digunakan adalah metode penelitian eksperimen dengan desain The One-Shot Case Study. Pengumpulan data dilakukandengan test. Data yang telah terkumpul selanjutnya diolah secara manual menggunakan rumus presentase. Hasilanalisis data menunjukkan bahwa terdapat peningkatan hasilbelajar sejarah siswa setelah menggunakan model Quantum Teaching.Kata kunci: hasil belajar, penerapan, quantum teaching